Cotton expansion and biodiversity loss in African savannahs, opportunities and challenges for conversation agriculture - (:unkn) unknown (My University, 2009)
34398 Montpellier cedex 5, France We review agricultural impacts on biodiversity and the potential of conservation agriculture in developing productive and environment-friendly cropping systems. We then analyse experiences from two African landscapes of global importance for conservation: the Mid Zambezi Valley in Southern Africa and the periphery of the ‘‘W-Arly- Penjari’’ complex in West Africa. In both areas, expansion of cotton farming, considered as one of the most polluting forms of agriculture in the world, drives major land use change and loss of biodiversity. In both areas, various forms of conservation agriculture have been developed and tested. We highlight the potential benefit of conservation agriculture in controlling negative environmental effects traditionally associated with agriculture and reducing the need for land conversion through increased biophysical resource use efficiency, turning agriculture from a threat to an opportunity for conservation. Finally, we raise a number of issues that constitute challenges for the widespread adoption of these technologies by resource-poor farmers, and formulate recommendations for the development, evaluation and diffusion of conservation agriculture technologies for smallholders in semi-arid Africa.
Keywords: African Research